The Influence of Video Modeling on Mother's Ability in Readiness to Implement Toilet Training in Toddler Age - Indra Rahmad; Julhana Julhana; Heni Nurhaeni; Saimi Saimi (Syntax Corporation Indonesia, 2023)
Toddler age (1-3 years) is a golden age because children in At this age, growth and development are very rapid. One of the tasks of toddler development is toilet training (Khaironi, 2018). Exercise CHAPTER or BAK in children really needs preparation for the mother, both physically, psychologically, and intellectually. Quantitative research with a quasi experimental approach with control group design. Research design pre-test and post-test control group design. The sampling technique was in the form of purposive sampling involving 100 respondents. The results of data analysis using the Wilcoxone test obtained a p-value of 0.000 (p <0.05) in the variables of knowledge, attitudes, mother's actions, and child's abilities. Before and after the intervention was given to the experimental group using video modeling. These results indicate that Ha is accepted and H0 is rejected so that it can be interpreted that there is an effect of giving video modeling on the knowledge, attitudes, actions of the mother, and the ability of the child in the readiness of the mother to carry out toilet training at toddler age. The results of statistical tests in the control group showed a value of 0.002 (p <0.05) on the knowledge variable, which means the value of toilet training ability in the control group there was an increase before and after it was given intervention. Then on the variables attitude, mother's actions, and children's abilities obtained by 0.001 (p <0.05) which means there was an increase before and after the intervention was given to the control group using the booklet.